USING PROJECT WORK IN TEACHING ENGLISH FOR SPECIFIC PURPOSES FOR ENERGY SE - Vilkhovchenko Nadiia (Alfred Nobel University Publisher, 2024)
This paper aims to investigate the efficacy of project-based learning in teaching English for specific purposes, particularly in technical universities within the energy sector. A number of methods helped to achieve this task. They include establishing the practical value of ESP for the energy sector and designing special methodology and training forms according to the tasks of the discipline. Our approach focuses on developing language skills by applying speaking abilities in practice in real-life situations that can facilitate learning English in a professional context. In this article, we examine two crucial components of project work: role-play and case study. These activities facilitate collaboration, communication, and problem-solving skills. Such kinds of projects help students expand their vocabulary and reinforce its usage in spoken English. Furthermore, presenting their findings and conclusions before their peers and teachers enhances their public speaking and presentation abilities. This paper advocates the use of project-based learning as a powerful tool for creating an immersive and meaningful language-learning experience. It showcases practical scenarios that students can simulate to enhance their learning experience. It also delves into the essential guidelines to ensure the success of this immersive teaching approach. In this paper, we provide a specific case study tailored for students in the energy sector, namely wind power integration in Ukraine. We detail the key stages of the implementation, the aims, and the critical highlights of this methodology. In the initial phase, the instructor should familiarize the students with new vocabulary and terminologies that are relevant to the renewable energy domain. It is recommended that students use industry-specific language in their discussions to augment their comprehension of the domain. This approach will help them build a solid foundation of the terminologies and lingo that are commonly employed in the renewable energy sector. The assignment objective is to provide a detailed and comprehensive overview of wind power as a renewable energy source in Ukraine, its prospects, and its feasibility. To accomplish this task, students must explore the intricacies of the project's technological challenges, as well as its economic impact and public perception. Furthermore, students must analyse communication strategies that have been utilized to influence public opinion, while considering the potential environmental impacts and anticipating sustainability project outcomes. For students to excel in this assignment, they must conduct thorough research and thoughtfully organize their findings. They must also evaluate all options, consider potential solutions, and justify their choices. Finally, students will be required to present their findings to the class in a polished and engaging manner. The presentation is expected to finish with group discussions. Following presentations and group discussions, students are encouraged to provide constructive feedback to their peers. This activity not only enhances their speaking skills but also promotes active listening and develops communication skills. In conclusion, to augment project work, elements such as role-play and case study methods can be integrated into ESP learning. Conclusions. This approach provides students in the energy sector with valuable insights into the challenges and dynamics of their industry while simultaneously enhancing their speaking skills. Teachers can supplement project work with multimedia resources such as videos, interviews, or documentaries related to the energy sector, which can add variety to the learning process and expose students to different accents and communication styles.